Factors affecting consumers' intention to purchase an electric vehicle in Klang Valley - Tai, Yee Yin (2024)
The purpose of this research is to identify the factors affecting consumers’ purchase intention of electric vehicles in Klang Valley, Malaysia. The researcher conducted the study based on a quantitative method and adapted convenience sampling method for data collection. The data were collected from 150 respondents living in Klang Valley who age 18 years old and above. The study adapted numerous analysis such as Correlation Analysis, Reliability Analysis and Multiple Linear Regression Analysis. The reliability of the research model was identified to be consistent and reliable and the correlation analysis revealed that only one out of five sociodemographics, income level and all independent variables correlate to the purchase intention of electric vehicles. The Multiple Linear Regression Analysis revealed that out of five predictors, only facilitating condition does not have a significant relationship with purchase intention. Financial factors, performance factors, income level, and environmental concerns is significantly affecting the purchase intention of electric vehicles.